Voice and Agency: Empowering Women and Girls for Shared Prosperity - JeniKlugman (World Bank, 2015)
Despite recent advances in important aspects of the lives of girls and women, pervasive challenges remain. These challenges reflect widespread deprivations and constraints and include epidemic levels of gender-based violence and discriminatory laws and norms that prevent women from owning property, being educated, and making meaningful decisions about their own lives--such as whether and when to marry or have children. These often violate their most basic rights and are magnified and multiplied by poverty and lack of education.